Management of Death Row Inmates, 1986-1987: (United States) - Hardy, Rauch W. ([Verlag nicht ermittelbar], 1993)
These data offer objective and subjective information about current death row inmates and the management policies and procedures related to their incarceration. The major objectives of the study were to gather data about the inmate population and current management policies and procedures, to identify issues facing correctional administrators in supervising the growing number of condemned inmates, and to offer options for improved management. Four survey instruments were developed: (1) a form for the Department of Corrections in each of the 37 states that had a capital punishment statute as of March 1986, (2) a form for each warden of an institution that housed death-sentenced inmates, (3) a form for staff members who worked with such inmates, and (4) a form for a sample of the inmates. The surveys included questions about inmate demographics (e.g., date of birth, sex, race, Hispanic origin, level of education, marital status, and number of children), the institutional facilities available to death row inmates, state laws pertaining to them, training for staff who deal with them, the usefulness of various counseling, medical, and recreational programs, whether the inmates expected to be executed, and the challenges in managing the death row population. The surveys did not probe legal, moral, or political arguments about the death penalty itself.